HMGA2 and protein leucine methylation drive pancreatic cancer lineage plasticity - Stephanie Dobersch; Naomi Yamamoto; Aidan Schutter; Sarah M. Cavender; Tess M. Robertson; Nithya Kartha; Annie N. Samraj; Ben Doron; Lisa A. Poole; Cynthia L. Wladyka; Amy Zhang; Gun Ho Jang; et al. (Nature Communications)
Abstract Basal pancreatic ductal adenocarcinoma (PDAC) has the worst overall survival and is the only subtype that serves as an independent poor prognostic factor. We identify elevated levels of LIN28B and its downstream target, HMGA2, in basal PDAC. Notably, LIN28B significantly accelerates KRAS-driven PDAC progression in a mouse model. Here, we show that HMGA2 promotes basal PDAC pathogenesis by enhancing mRNA translation downstream of LIN28B. Mechanistically, HMGA2 suppresses leucine carboxyl methyltransferase 1 (LCMT1) at the chromatin level, reducing PP2A methylation and activity. This leads to increased phosphorylation of S6K and eIF4B, boosting mRNA translation. Additionally, HMGA2 downregulates B56α (PPP2R5A), disrupting functional PP2A holoenzyme assembly and further sustaining phosphorylated S6K levels. Impaired PP2A function mimics HMGA2’s effects, reinforcing increased mRNA translation and basal lineage features. This work uncovers a critical link between the LIN28B/HMGA2 axis, protein synthesis, and PDAC lineage specificity via LCMT1-mediated PP2A methylation and B56α-PP2A disruption.